Building Brand Commitment, Brand Loyalty, and Willingness to Pay Premium Price of Citraland Ambon Properties Through Brand Credibility - Tabelessy, Walter (International Journal of Contemporary Sciences (IJCS), 2025)
This study analyzes the influence of brand credibility on brand commitment, brand loyalty, and willingness to pay a premium price among consumers of Citraland Ambon properties. Using the SEM-GSCA approach and purposive sampling, the results reveal that brand credibility has a significant positive impact on brand commitment. In turn, brand commitment influences brand loyalty and willingness to pay a premium price. Additionally, brand loyalty positively affects willingness to pay a premium price. The model fit test indicates a good model with high reliability and validity. These findings affirm that brand credibility is a key factor in building brand commitment, brand loyalty, and willingness to pay a premium price. This study provides valuable insights for brand management in the property industry, particularly for Citraland Ambon, and opens opportunities for further research on marketing strategies that enhance brand credibility and brand loyalty.